2013
DOI: 10.3103/s0967091213110065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the quenching temperature on the phase composition, structure, and wear resistance of 150XHM steel

Abstract: The prevention of abrasive wear is of great impor tance, since such wear can cause premature failure of components in mining, metallurgical, construction, and drilling equipment. We are particularly interested in the cylindrical bushes of borehole pumps, which are subject to cyclic loads at high variable pressure, as well as the abrasive action of borehole fluid with suspended solid particles. The complex loading results in rapid bush failure, on account of hydroabrasive wear and the appearance of impermissibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…The mentioned features of the influence of t quen on the wear resistance of 150KhNML steel confirm the published data about the positive role of residual austenite of a certain composition and its metastability with regard to deformation-induced martensite transformation in provision of high abrasion resistance [2]. The increase in wear resistance is stipulated by the increase in the content of deformation α martensite with a high carbon content on the wear surface with an increase in t quen and by an increase in the ability of residual austenite to friction hardening.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…The mentioned features of the influence of t quen on the wear resistance of 150KhNML steel confirm the published data about the positive role of residual austenite of a certain composition and its metastability with regard to deformation-induced martensite transformation in provision of high abrasion resistance [2]. The increase in wear resistance is stipulated by the increase in the content of deformation α martensite with a high carbon content on the wear surface with an increase in t quen and by an increase in the ability of residual austenite to friction hardening.…”
Section: Methodssupporting
confidence: 85%
“…However, a higher cost and technologically efficient variant is provided by monolith fabrication from tool steels, for instance, 150KhNML pearlitic steel. It was demonstrated that high temperature quenching can improve abrasion resistance of Kh12MF and 150KhNML steels with approximately the same carbon content of 1.5% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Tables 2 -4 also show variations of heating temperatures (HT) and soaking times (ST). The ranges of temperature used in the present study were less than that of Filippow et al [13]. They used a temperature range of 800°C and 1200°C and observed that there was a drop in hardness as the quenching temperatures increases.…”
Section: Resultsmentioning
confidence: 72%
“…2) обес-печивает высокую твердость (61 HRC). Однако максимальная износостойкость при абразивном изнашивании достигается после высокотемпературной закалки стали (1100÷1175 °С), формирующей мартенситно-карбидную структуру с метастабильным аустенитом в количестве 10-15 % и высокой способностью к фрикционному упрочнению [15][16][17][18][19][20].…”
Section: результаты исследованийunclassified